2013
DOI: 10.1038/ng.2635
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nine new susceptibility loci for testicular cancer, including variants near DAZL and PRDM14

Abstract: Testicular germ cell tumor (TGCT) is the most common cancer in young men and is notable for its high familial risks1,2. To date, six loci associated with TGCT have been reported3-7. From GWAS analysis of 307,291 SNPs in 986 cases and 4,946 controls, we selected for follow-up 694 SNPs, which we genotyped in a further 1,064 TGCT cases and 10,082 controls from the UK. We identified SNPs at nine new loci showing association with TGCT (P<5×10−8), at 1q22, 1q24.1, 3p24.3, 4q24, 5q31.1, 8q13.3, 16q12.1, 17q22 and 21q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 46 publications
3
138
0
Order By: Relevance
“…In comparison, activating KIT mutations appear in approximately 20% of seminomas (1), whereas multiple GWAS-identified loci associated with TGCT account altogether for approximately 25% to 32% of the genetic risk of developing TGCT (4,5). In this context, the ubiquitous occurrence of the RHAMM defect raises the possibility that RHAMM represents a convergence hub of the activity of multiple TGCT ÃÃÃ , P < 0.0001 (P ¼ 0.0000027); ÃÃ , P < 0.01 (P ¼ 0.0024).…”
Section: Rhamm Downregulation and Delocalization From The Spindle Appmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, activating KIT mutations appear in approximately 20% of seminomas (1), whereas multiple GWAS-identified loci associated with TGCT account altogether for approximately 25% to 32% of the genetic risk of developing TGCT (4,5). In this context, the ubiquitous occurrence of the RHAMM defect raises the possibility that RHAMM represents a convergence hub of the activity of multiple TGCT ÃÃÃ , P < 0.0001 (P ¼ 0.0000027); ÃÃ , P < 0.01 (P ¼ 0.0024).…”
Section: Rhamm Downregulation and Delocalization From The Spindle Appmentioning
confidence: 99%
“…Despite extensive research, the etiology of TGCT is not well understood. Loss of heterozygosity, allelic imbalance, and genome-wide association studies (GWAS) have identified several loci and genes conferring TGCT susceptibility; however, most of them are not functionally characterized (4)(5)(6)(7). On the basis of these and other data, models of TGCT development have been proposed (8) but the initiating event behind these cancers remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) in humans identified susceptibility loci such as KIT ligand (KITL), Sprouty 4 (SPRY4), Bcl2 antagonist killer (BAK1), Doublesex-and Mab3-related transcription factor (DMRT1), Deleted in azoospermia RNA-binding protein (DAZL), PRDM transcriptional regulator (PRDM14), the telomerase reverse transcriptase TERT, and its cofactor AFT7IP (9)(10)(11)(12)(13)(14)(15). Individually and collectively, however, these susceptibility genes account for only a modest portion of inherited risk.…”
mentioning
confidence: 99%
“…Variants have been found near genes involved in male germ cell development (DAZL, HPGDS, SMARCAD1, SEPT4, TEX14, RAD51C, PPM1E, and TRIM37), chro mosomal segregation (MAD1L1, TEX14, and SKA2), the DNA damage response (SMARCAD1, RFWD3, and RAD51C), and epigenetic regulation (JMJD1C/KDM3A and KDM2A) [83,85,91] . Mouse models would help to evaluate the roles of these genes in the tumorigenesis of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, PGClike cells induced from homozygous Tfap2c mutant ESCs show upregulation of cell cycle regulators (Cdk6) and pluripotency genes (Eras, Klf4), but downregulation of germline genes (Dmrt1, Nanos3) [84] . Furthermore, the susceptibility locus for human testicular germ cell cancer has been found near PRDM14 [85] . Collectively, these germline genes also function as gatekeepers of PGC dedifferentiation.…”
Section: Regulators Of Germ Cell Developmentmentioning
confidence: 99%